Low iodine diet advice and differentiated thyroid cancer treatment: A historic exploration in three UK centres. (February 2022) - England, Clare; Ingarfield-Herbert, Kate; Beasley, Matthew; Moss, Laura; Vinjamuri, Sobhan; Haupt-Schott, Ingrid; McKane, Gail; Hunt, Linda; Herbert, Georgia; Leary, Sam; Ness, Andy; Atkinson, Charlotte
Summary: Background and aims: Patients with differentiated thyroid cancer are often advised to follow a low iodine diet (LID) one to two weeks before radioiodine remnant ablation (RRA). We describe treatment practices and ablation success rates in centres (C1, C2, C3) in the UK with different approaches to LID advice. Methods: Historic cohort of patients with differentiated thyroid cancer treated with RRA in 2015/16 in C1 (n = 50, 1-week LID), C2 (n = 59, 2-week LID) and C3 (n = 108, no LID advice). Response to RRA was stratified as excellent, indeterminate, or incomplete by the adapted American Thyroid Association Dynamic Risk Stratification Score. Results: There was little difference in age, sex and staging between centres, but the percentage receiving 1.1 GBq vs higher administered activities differed (C1:22%, C2:44%, C3:15%, p < 0.001). Excellent response was recorded for: C1:48%, C2:36%, C3:49% (p = 0.61). Differences in RRA preparation and outcome assessment at C3 precluded comparison across all centres. Adjusted odds ratio for excellent response at C2 vs C1 was 0.57 (95%CI: 0.25, 1.32), p = 0.19. Conclusions: There was no evidence that advising a LID for 2-weeks before RRA improves outcomes compared to 1-week. For definitive recommendations on LIDs prior to RRA, a prospective multi-centre study with a more homogenous approach to patient management or, randomised controlled trial, is needed.